2011
DOI: 10.1111/j.1755-263x.2011.00205.x
|View full text |Cite
|
Sign up to set email alerts
|

Conserving imperiled species: a comparison of the IUCN Red List and U.S. Endangered Species Act

Abstract: The United States conserves imperiled species with the Endangered Species Act (ESA). No studies have evaluated the ESA's coverage of species on the International Union for Conservation of Nature (IUCN) Red List, which is an accepted standard for imperiled species classification. We assessed the ESA's coverage of IUCN-listed birds, mammals, amphibians, gastropods, crustaceans, and insects, and studied the listing histories of three bird species and Pacific salmonids in more detail. We found that 40.3% of IUCN-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 30 publications
1
38
0
Order By: Relevance
“…As innovations occur in marine conservation and planning (Campagna et al 2007, Stelzenmuller et al 2013, we require accurate biological information on which to base new conservation strategies. While we aspire to manage optimally, acting before species or ecosystems are lost means we must manage using the levers we can pull, such as the CITES and the US Endangered Species Act (Harris 2012). Levers also exist where international, national, regional, and local entities are creating and modifying laws, rules, and customs for the management of fisheries and the conservation of ecosystems (Weeks et al 2014).…”
Section: Empowering Conservation Actionsmentioning
confidence: 99%
“…As innovations occur in marine conservation and planning (Campagna et al 2007, Stelzenmuller et al 2013, we require accurate biological information on which to base new conservation strategies. While we aspire to manage optimally, acting before species or ecosystems are lost means we must manage using the levers we can pull, such as the CITES and the US Endangered Species Act (Harris 2012). Levers also exist where international, national, regional, and local entities are creating and modifying laws, rules, and customs for the management of fisheries and the conservation of ecosystems (Weeks et al 2014).…”
Section: Empowering Conservation Actionsmentioning
confidence: 99%
“…Although the IUCN is often regarded as the world's primary authority on the conservation status of species (Mrosovsky 1997), within the United States federal protections are not established until they are listed under the Endangered Species Act. For Bog Turtles, ESA listing came the following year (although only for the northern populations), but for most IUCNlisted species ESA listing has never followed (Harris et al 2011). Unfortunately, delayed prioritization and protections can leave managers with fewer conservation options with potentially greater uncertainty regarding their outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…So, the assessment of biodiversity of Finland (Juslén et al, 2013), birds of Britain (Eaton et al, 2005) or Switzerland (Keller et al, 2005), butterflies of Flanders (Maes et al, 2012), re-assessment of 163 rare species of Asian countries (Millner-Gulland et al, 2006) did not provoke serious disagreements with IUCN schemes. On the contrary, comparison of the IUCN list with US Endangered species act (Harris et al, 2013) or with the red lists of Brazil, Colombia, China and the Philippines (Brito et al, 2010) revealed numerous mismatches. Analysis of not well studied invertebrates showed, that IUCN criteria are not applicable for them (Cardoso et al, 2012).…”
Section: Discussionmentioning
confidence: 99%